2017
DOI: 10.4103/ijnmr.ijnmr_92_16
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effect of echinacea and chlorhexidine mouthwash on the microbial flora of intubated patients admitted to the intensive care unit

Abstract: Background:Providing intubated patients admitted to the intensive care units with oral healthcare is one of the main tasks of nurses in order to prevent Ventilator-Associated Pneumonia (VAP). This study aimed at comparing the effects of two mouthwash solutions (echinacea and chlorhexidine) on the oral microbial flora of patients hospitalized in the intensive care units.Materials and Methods:In this clinical trial, 70 patients aged between18 and 65 years undergoing tracheal intubation through the mouth in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
1
11
0
6
Order By: Relevance
“…Thus, a score of 5 means no disorder, 6 -10 means a mild disorder, 11 -15 means a moderate disorder, and 16 -20 means a severe disorder. Safarabadi et al (9) confirmed the scale's validity and reliability using the test-retest method with a Pearson correlation coefficient of 0.92. In the present study, the scale's reliability was confirmed using the inter-rater reliability method with a coefficient of 0.93.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, a score of 5 means no disorder, 6 -10 means a mild disorder, 11 -15 means a moderate disorder, and 16 -20 means a severe disorder. Safarabadi et al (9) confirmed the scale's validity and reliability using the test-retest method with a Pearson correlation coefficient of 0.92. In the present study, the scale's reliability was confirmed using the inter-rater reliability method with a coefficient of 0.93.…”
Section: Methodsmentioning
confidence: 93%
“…It is generally accepted that "good and frequent oral care" is more important for these patients and can be provided by several separate or combined methods such as mouthwash, gel use, toothbrush, and secretion suction (8). Safarabadi et al (9) quotes Grap and Munro that oral health and care should be considered as one of the most significant components of nursing care.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the components of BOAS, which is brought from the study of Nguh (2016) [12]. Safarabadi et al (2017) confirmed the validity and reliability of the BOAS tool, in which content validity was supported by three anesthesiologists, two neurosurgeons, and five expert nurses working in ICUs. The testretest method has been used to determine its reliability by evaluating twenty ICU patients by two observers separately, and a correlation coefficient of 0.92 was obtained [13].…”
Section: Methodsmentioning
confidence: 68%
“…Results of a study of hospitalized patients have also shown that pathogenic microorganisms are present in patients’ mouths from day one and show an increasing trend during hospitalization [ 35 ]. Therefore, it seems that the use of CHX in COVID-19 patients who have altered oral flora, whether in a hospital or non-hospital setting is an important procedure to improve the symptoms in these patients [ 25 , 36 ].…”
Section: Chlorhexidine (Chx)mentioning
confidence: 99%